Tumor necrosis factor is elevated in progressive multiple sclerosis and causes excitotoxic neurodegeneration. (March 2014) - Rossi, Silvia; Motta, Caterina; Studer, Valeria; Barbieri, Francesca; Buttari, Fabio; Bergami, Alessandra; Sancesario, Giulia; Bernardini, Sergio; De Angelis, Gottardo; Martino, Gianvito; Furlan, Roberto; Centonze, Diego
Background: Chronic inflammation leads to gray matter damage in progressive multiple sclerosis (MS), but the mechanism linking inflammation and neurodegeneration is unclear. Objective: The objective of this paper is to investigate the synaptic mechanism of inflammatory neurodegeneration in progressive forms of MS. Methods: Cytokine and neurofilament-light were determined in cerebrospinal fluid (CSF) of MS patients. In vitro electrophysiology and cell swelling experiments were performed to measure the effects of inflammatory cytokines in the CSF of MS patients on synaptic transmission and neuronal integrity. Results: Tumor necrosis factor-α (TNF) was higher in CSF of progressive MS subjects, and caused excitotoxic neuronal death in vitro. In murine brain slices incubated in the presence of CSF from progressive MS, in fact, we observed increased spontaneous excitatory postsynaptic currents (sEPSCs) and glutamate-mediated neuronal swelling through a mechanism dependent on enhanced TNF signaling. We also suggested a pathogenic role of B cells in TNF CSF increase, exacerbation of glutamatergic transmission and neuronal damage, since CNS depletion of B cells with intrathecal rituximab caused a dramatic reduction of TNF levels, of TNF-induced sEPSC alterations, and of neurofilament CSF concentrations in a patient with progressive MS. Conclusion: Our results point to TNF as a primary neurotoxic molecule in progressive forms of MS.